2012
DOI: 10.1111/j.1751-7176.2011.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of Hospitalizations Associated With Thiazide‐Associated Hyponatremia

Abstract: The prevalence of hypertension in the United States has grown dramatically in recent years. Thiazide diuretics have played a major role in the rising rate of blood pressure (BP) control. Accompanying this has been the appearance of adverse drug events, including hospitalizations associated with thiazide-associated hyponatremia (HTAH). Hyponatremia is a common yet often overlooked side effect of this drug class. Identification of HTAH risk factors may aid in creating strategies to prevent hospitalizations. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…Hyponatremia, which results from a multitude of causes besides medications, can manifest as delirium, falls, lethargy, stupor, and even seizures, based on the severity and acuity of development. Predisposing factors include increasing age, female sex, larger dose of thiazide or thiazide-like diuretics, presence of hypokalemia, and lower body mass index; different studies suggest the influence of ACEIs to be a predisposition and otherwise [28,[42][43][44][45][46][47][48][49]. In a given individual, besides diuretics, there may well exist other causes for hyponatremia, such as water retention caused by excessive water intake, psychogenic polydipsia, heavy beer intake, and impaired water-excreting ability [50].…”
Section: Diureticsmentioning
confidence: 96%
See 1 more Smart Citation
“…Hyponatremia, which results from a multitude of causes besides medications, can manifest as delirium, falls, lethargy, stupor, and even seizures, based on the severity and acuity of development. Predisposing factors include increasing age, female sex, larger dose of thiazide or thiazide-like diuretics, presence of hypokalemia, and lower body mass index; different studies suggest the influence of ACEIs to be a predisposition and otherwise [28,[42][43][44][45][46][47][48][49]. In a given individual, besides diuretics, there may well exist other causes for hyponatremia, such as water retention caused by excessive water intake, psychogenic polydipsia, heavy beer intake, and impaired water-excreting ability [50].…”
Section: Diureticsmentioning
confidence: 96%
“…A study has suggested that risks included home institutionalization and physical immobility; duration of thiazide use; concomitant use of loop diuretics; body weight (increased mass decreased the odds); while the use of ACEIs and NSAIDs and renal function bore no association [46]. While hyponatremia clearly occurs with thiazide use and increases with age, views on other predispositions vary or contradict based on a given study [47][48][49]. Indapamide use is associated with hyponatremia [52].…”
Section: Diureticsmentioning
confidence: 99%
“…27 The associated use of angiotensin converting enzyme inhibitors (ACEi), 42 or angiotensin II receptor blockers (ARBs) 43 can increase the risk and/or severity of hyponatraemia, as can hypokalaemia. 42 We have observed that close to 60% of elderly patients with marked thiazide-related hyponatraemia are hypovolaemic, as classified by an initial physical examination that includes OP and CVP, with the remaining 40% euvolaemic. 44 In 27 elderly patients (median age 80 years; range 65-84 years) with a median initial S Na of 116 mmol l −1 (109-119), urinary Na tended to be lower in the hypovolaemic group: 40 mmol l −1 (18-69) vs 61 mmol l −1 (43-85) (P = 0.09).…”
Section: Physical Examinationmentioning
confidence: 99%
“…In case 3, the patient restricted his salt intake due to hypochondria for one year, which may have played a role in increasing the severity of the hyponatremia. Rastogi et al pointed out that risk factors, such as age, ACE inhibitor use and hypokalemia, are profoundly associated with thiazide-induced hyponatremia (17). Preventing thiazide-induced hyponatremia is important, and carefully monitoring the serum sodium level, providing counseling regarding water intake and administering the lowest possible dosage of thiazide will reduce the risk of the disease (18).…”
Section: Discussionmentioning
confidence: 99%